PECULIARITIES OF INFORMATION SUPPORT FOR ENTERPRISE MANAGEMENT - MYKOLIUK, OKSANA; BOBROVNYK, VALENTYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes the role of information, which is to ensure the ability of senior management to respond in a timely and adequate manner to global economic challenges in order to quickly and efficiently make appropriate management decisions. It is emphasized that an important factor in achieving the goals of sustainable development of both society and the individual enterprise is the timely provision of reliable, necessary and sufficient information. The role of approaches to understanding the essence of information support is specified, and also classification characteristics of information resources of the enterprise are revealed. The relationship between the perfection of the management system and the information system is revealed. The external and internal information resources of the enterprise are outlined and the possibilities of their use in the development of the enterprise on the basis of the use of modern digital technologies are determined. It is proved that the quality and efficiency of information support significantly affects the effectiveness of any management technology. It is substantiated that the formation of information support is a rather complex and multifaceted process of providing a convenient and effective form of information exchange both inside the company and outside. The role of effective functioning of information support coming from three main sources is emphasized: enterprise information; information from the media and information from consulting firms. The problem of creating information support for enterprise management in order to form new prospects for their further development is actualized. The conclusion is made about the need to create a modern information infrastructure, which is a priority for the development of the business sector.
Keywords: enterprise management; information support; enterprise development; information resources; competitiveness